Research Highlights in Mathematics and Computer Science Vol. 1 - Ferreira, M. A. M. (2022)
This book covers key areas of Mathematics and Computer Science. The contributions by the authors include Bayes approach, bayes’ method, markov chain monte carlo method, Fuzzy Set , Fuzzy Subring , Fuzzy Normal Subring , Fuzzy Ideal , X-Fuzzy Ideal , Semiprime-factorization, cryptography, PLS regression, latent structure regression, ridge regression, H-principle of mathematical modelling, H-methods, stochastic perturbations, stochastic dierential equation, linearization, asymptotic mean square stability, stability in probability, stability regions, glassy-winged sharpshooter population, Recurrent C0-semigroups, subspace-recurrent C0-semigroups, recurrence criteria, recurrent vectors, hypercyclic C0-semigroups, direct sum, idempotents, integral domain, Fixed point, game theory, Nash equilibrium, and code optimization. This book contains various materials suitable for students, researchers and academicians in the field of Mathematics and Computer Science.